2020
DOI: 10.1021/acs.jafc.0c05028
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Agroindustrial Wastes to Rhamnolipid by Enterobacter sp. UJS-RC and Its Role against Biofilm-Forming Foodborne Pathogens

Abstract: Rhamnolipid is the main group of biosurfactants predominantly produced by Pseudomonas aeruginosa, a ubiquitous and opportunistic pathogen, which limits its large-scale exploitation. Thus, cost-effective rhamnolipid production from a newly isolated nonpathogenic Enterobacter sp. UJS-RC was investigated. The highest rhamnolipid production (4.4 ± 0.2 g/L) was achieved in a medium constituting agroindustrial wastes (sugarcane molasses and corn steep liquor) as substrates. Rhamnolipid exhibited reduced surface tens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 45 publications
0
7
0
1
Order By: Relevance
“…Efficient bactericidal activity is one of the most important features of an effective antibacterial agent . The bactericidal performance of active molecule 7d (6 × MIC and 8 × MIC) against S.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Efficient bactericidal activity is one of the most important features of an effective antibacterial agent . The bactericidal performance of active molecule 7d (6 × MIC and 8 × MIC) against S.…”
Section: Resultsmentioning
confidence: 99%
“…Efficient bactericidal activity is one of the most important features of an effective antibacterial agent. 36 The bactericidal performance of active molecule 7d (6 × MIC and 8 × MIC) against S. aureus ATCC 29213 (early and late exponential phases) was evaluated, and the results are recorded in Figure 3. Compound 7d could rapidly kill early exponential phase S. aureus ATCC 29213 (2 h, 6 × MIC; 1 h, 8 × MIC), and the late exponential phase bacteria were also killed in the presence of molecule 7d (5 h, 6 × MIC; 3 h, 8 × MIC).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…N18, using yeast extract and sucrose as substrates (You, et al, 2015) and Enterobacter sp. UJS-RC using corn steep liquor and sugarcane molasses as alternative sources (Chandankere, et al, 2020) (Table 3). Recently, Ekprasert et al ( 2021) reported higher biosurfactant production by E. cloacae B14 using waste frying oil, compared to other agro-industrial wastes (spent coffee grounds and molasses), confirming the suitability of this alternative substrate.…”
Section: Biosurfactant Production By Enterobacter Cloacae Ucp 1597 Us...mentioning
confidence: 99%
“…As a growing public health problem throughout the world, foodborne diseases (FBDs) have resulted in almost 1 in 10 people being ill, leading to 420,000 deaths every year (Chandankere et al, 2020 ; Li et al, 2020 ). Among them, FBDs caused by Campylobacter pylori, Staphylococcus aureus, Listeria monocytogenes, Escherichia coli, Vibrio parahaemolyticus, Salmonella cholerae, Proteus mirabilis, Shigella flexneri , and other foodborne bacteria (FBB) have been widely reported and are of great concern (Tack et al, 2019 , 2020 ).…”
Section: Introductionmentioning
confidence: 99%